2017
DOI: 10.1007/s10802-017-0273-x
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Conduct Disorder and Callous Unemotional Traits: Preliminary Results of a School Based Pilot Training Program

Abstract: This study investigated whether a school-based pilot prevention program is effective in reducing Conduct Disorder (CD) symptoms and callous unemotional (CU) traits (i.e., lack of empathy and guilt) in a community sample of children. A total of 304 children from three schools in Cyprus were randomly assigned at school level to either a prevention group that received a skill building training program (N = 94; M = 7.91, SD = .74; 52.1% female) or a control group that received no training (N = 210; M = 7.82, SD = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 51 publications
0
25
0
1
Order By: Relevance
“…Accordingly, it suggests that such traits help to understand engagement in RB across cultures (Essau et al, ; Fanti et al, ; Frick et al, ). Notwithstanding other important unexamined factors known to contribute to relational bullying and victimization, our findings suggest that prevention efforts should consider CU traits in order to protect youth from relational bullying (see Kyranides et al, ). Prevention efforts focusing on enhancing students’ empathy might result in decreased relational bullying and victimization, although cultural and gender differences should also be considered.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Accordingly, it suggests that such traits help to understand engagement in RB across cultures (Essau et al, ; Fanti et al, ; Frick et al, ). Notwithstanding other important unexamined factors known to contribute to relational bullying and victimization, our findings suggest that prevention efforts should consider CU traits in order to protect youth from relational bullying (see Kyranides et al, ). Prevention efforts focusing on enhancing students’ empathy might result in decreased relational bullying and victimization, although cultural and gender differences should also be considered.…”
Section: Discussionmentioning
confidence: 70%
“…Although youth scoring high on CU traits are less likely to respond to traditional intervention compared to antisocial youth low on CU traits, initial evidence has indicated that various preventions and interventions have been proved effective in reducing their problematic behaviors (Hawes & Dadds, ). A study conducted in Cyprus suggested that school preventions focusing on enhancing empathy and emotion regulation can decrease both antisocial behaviors and CU traits (Kyranides et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, ICU scores demonstrated adequate internal consistency across all three assessment points (α 1 = 0.77, α 2 = 0.80, α 3 = 0.89). The reliability and construct validity of the Greek version of the ICU that have been supported by prior work [32,34].…”
Section: Methodsmentioning
confidence: 68%
“…However, violence and BP relationship is even more complex and multidirectional. While on the one hand, environmental stressors in periods of greater vulnerability, such as maltreatment and growing in violent communities and schools, significantly increase chances of developing BP (2)(3)(4) , on the other hand, once BP is started, there is a greater chance of developing mood, anxiety, and chemical dependency disorders, as well as dropping out of school before high school, engaging in violence and crime, and failing to enter the market work in adult life (5)(6)(7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%